Impact of High Temperature Stress in Rice - Umarani, E.; Hemalatha, V.; Saritha, A.; Ramanjaneyulu, A. V. (International Journal of Economic Plants, 2020)
Global warming has become a big concern in the world and it has been continuously increasing in recent decades due to the greenhouse effect. The increase in temperature has been striking and it can cause irreversible damage to plant growth and development. Though rice originates from the tropics, high temperatures of more than 35 °C during the reproductive stages reduces rice production, especially when the rice plant flowers when the high temperature occurs because it causes low seed setting and low yield. It was found that rice grain yield declined by 10% for each 1 °C increase in growing-season minimum temperature. Early-morning flowering is an important criteria in rice which escapes plant from high temperatures during peak period. It was found that Oryza glaberrima, a wild species of rice, is a useful genetic source since it has a habit of early-morning flowering and high transpiration with sufficient water, both of which are convenient traits for avoiding heat stress.